Evaluasi Peraturan Daerah Nomor 3 Tahun 2016 Tentang Penataan dan Pemberdayaan Pedagang Kaki Lima: Studi Kasus di Kawasan Gading Fajar Kabupaten Sidoarjo - Nadea Legitasari; Yusuf Hariyoko; Wahid Hidayat (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The issue of street vendors (PKL) in Sidoarjo Regency, particularly in the Gading Fajar area, has become a significant concern as it relates to public order, the use of public space, and the economic dynamics of small communities. To address these challenges, the Sidoarjo Regency Government enacted Regional Regulation Number 3 of 2016 as the legal basis for structuring and empowering PKL. This study examines how the regulation is implemented in practice and evaluates its effectiveness using a qualitative descriptive method through interviews, observations, and documentation, analyzed with Leo Agustino’s policy evaluation model, which assesses five key aspects: administrative resources, institutional coordination, infrastructure and technology, financial support, and regulatory adequacy. The findings show that the implementation of the regulation has not yet reached optimal performance, as limited socialization, insufficient personnel, weak coordination among agencies, inadequate supporting facilities, and low compliance with zoning rules hinder the achievement of policy objectives. These issues are reflected in the continued presence of PKL operating in non-designated areas despite clear regulatory provisions. Therefore, strengthening institutional capacity, improving facilities, enhancing enforcement consistency, and developing more operational technical guidelines are essential to ensure more effective and sustainable management and empowerment of street vendors in Sidoarjo Regency.